PERSEPSI PESANGGEM TERHADAP ASPEK EKONOMI DAN EKOLOGI HUTAN di KABUPATEN BLITAR - Wahyu Budiman, Eko (Universitas Islam Balitar, 2019)
Forests are natural resources that provide benefits to human welfare, both directly (intangible) and indirectly (tangible). The existence of forests in this case as a carrying capacity for all aspects of human life, animals and plants is largely determined by the low level of human awareness of the importance of forests in the use and management of forests. This research was conducted with the aim of finding out the perceptions of participants in looking at the ecology and economic value produced by forests and as a consideration in determining the pesanggem decisions and to find out the approach to forest area farming to support the welfare of the community. This research was in Blitar, precisely Wonotirto District and Bakung District. Analysis of the data used is descriptive analysis of assessment scores, while to know sugarcane income is to use analysis of income and farm income. The results of the study concluded that the perception of the pesanggem on the ecology and economy of the forest was positive, although there were some pesanggem who had negative perceptions. While the analysis of farm income per ha is Rp. 26,829,023, - with a total cost per Ha of Rp. 10,602,351, - get a profit of 16,226,672, -, the calculation of R / C Ratio is 2.49 so farming is efficient to run. Production Break Event Point (BEP) is 30,293 Kg and Break Event Point (BEP) price of Rp.139 / Kg, so customers must increase production if they want to get more profits.